Impact of organizational health-oriented strategies on employees' job performance, perceived medical mistrust as a moderator: A COVID-19 perception-based view - Ye, Mao; Chen, Yu; Liu, Yang; Li, Xiaohuan (Frontiers in Public Health, 2022)
Employees are considered an asset of the firm because they can play a crucial role in making or breaking the brand. After experiencing the COVID-19 pandemic, employees’ health and well-being become a priority for firms. Organizational health-oriented strategies assist them in coping with health-related crises. Organizational health-oriented strategies have a considerable role in boosting employees’ well-being and building their trust. Based on the social exchange theory, the present study attempts to determine the role of organizational health-oriented strategies in promoting employees’ job performance. This study explores the role of organizations' health-oriented strategies on employees' job performance through mediating role of employees' psychological well-being and trust. This study also assessed the moderating role of perceived medical mistrust between employees' psychological well-being and their job performance and employees' trust and their job performance. For the empirical examination, data of the present study was gathered from the textile sector in China. This study analyzed data through partial least square structural equation modeling (PLS-SEM). For this purpose, SmartPLS software was used. The outcomes revealed that organizational health-oriented strategies positively enhance the employees' psychological well-being and trust, and in turn, employees' psychological well-being and trust positively influence their job performance. Moreover, employees' psychological well-being and employee trust positively mediate the relationship between organizational health-oriented strategies and employees' job performance. This study found that perceived medical mistrust moderates the relationship between employees' psychological well-being and job performance but does not moderate the relationship between employees' trust and job performance. In addition, the findings of the present study provide insights to the firms about the importance of health-oriented strategies. Moreover, the findings of the present study also serve the literature by providing important theoretical and practical implications.